Over‐current protection method for PMSM VSI with small DC‐link capacitor. Issue 7 (1st June 2018) - Xu, Yongxiang; Huang, Yingliang; Zheng, Boyuan; Zhang, Wentao; Li, Yong; Zou, Jibin
Abstract : In this study, an over‐current protection method for permanent magnet synchronous motor (PMSM) voltage source inverter (VSI) employing small DC‐link capacitor is proposed. Since VSI with small DC‐link capacitor has become popular for its long lifetime and compactness. However, the small DC‐link capacitor brings the risk of excessive voltage in the DC‐link capacitor when the traditional 'all‐turn‐off' over‐current protection is utilised. In order to avoid the damage for VSI caused by excessive pumping‐up voltage, based on the analysis for the 'all‐turn‐off' method, the proposed method could eliminate reversal current flowing into the DC‐link capacitor through switching logic. Consequently, the electro‐magnetic energy stored in PMSM windings is converted into mechanical energy and pumping‐up voltage is cancelled. Detailed analysis of the proposed method is presented. The effectiveness of the proposed method is verified by simulation and experiments.